The Empowerment of International Community Service Program Students in Supporting Learning Activities at Sanggar Guidance of Sekolah Indonedia Kuala Lumpur, Kuala Lumpur, Malaysia - Ainun Mardhiah, S. PdI, M. Pd; Geubrina Maghfirah; Abubakar; Dessi Nur Adiska; Zainuddin; Muhammad Zulfajri; M. Nurrijal; Aldiyat Luthfianda; Birrul Walidain (Kodepena Indonesia, 2026)
This study aims to analyze the forms of empowerment of International Community Service Program students in supporting learning activities at SB Pantai Dalam Kuala Lumpur, Malaysia.This study employed a qualitative approach using a descriptive method. Data were collected through observations, in-depth interviews with teachers, International Community Service Program students, and Sanggar Bimbingan administrators, as well as documentation studies of learning activities. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, with triangulation techniques applied to ensure the validity of the findings.The results indicate that International Community Service Program students contributed to improving the quality of learning through assistance in teaching and learning activities, the development of creative learning media, the implementation of student-centered learning methods, the strengthening of literacy and numeracy skills, and the implementation of character education activities. The presence of students also increased learners' motivation, strengthened collaboration with teachers, and created a more active, interactive, and conducive learning environment.This study concludes that the empowerment of International Community Service Program students provides a significant contribution to improving the quality of educational services at SB Pantai Dalam and strengthens the implementation of community engagement programs within the context of international education for Indonesian diaspora children